Applying cooperative learning principles to the teaching of English speaking skills in large classes = Ứng dụng các nguyên lý học hợp tác vào việc dạy kỹ năng nói tiếng Anh cho các lớp đông. M.A Thesis Linguistics : 60 14 10 - Nguyễn, Thị Xuân Hương (University of Languages and International Studies, 2017)
43 p. + CD-ROM